Hubungan Pengetahuan dan Sikap terhadap Perilaku Perawat dalam Perencanaan Pasien Pulang (Discharge Planning) - Sri Rahayu (Faletehan Health Journal, 2024)
Patient discharge planning is a crucial aspect of healthcare, yet the implementation in hospitals was not optimal by nursing teams. This research aimed to explore the relationship between the level of knowledge and attitude of nurses with the implementation of discharge planning in inpatient ward. The research method employed was a cross-sectional design with the total sample of 68 nurses selected through total sampling technique. The data collection was conducted through interviews and a questionnaire as the research instrument. The data analysis was performed by using chi-square test. The results of this study indicated a significant relationship between nurse knowledge (p<0.000) and attitude (p<0.000) with the implementation of discharge planning. The researcher recommended that discharge planning practices should be maintained, improved, and applied comprehensively from admission to patient discharge.